Vergi usul hukukunda usulsüzlük fiilleri ve yaptırımları - Badem, Harun (My University, 2020)
Çağdaş vergi sistemlerinde benimsendiği gibi Türk Vergi Sistemi de beyan esasına dayanır. Beyana dayalı tam ve adil bir vergilendirme yapılabilmesi de buna dayanak oluşturan bilgi ve belgelerin gerçeğe uygun olması ile mümkündür. Bunun yanı sıra bilgi-belge düzenlenmesi ve bilgi-belgelerin bildirilmesinin de şekil ve usul kurallarına uygun olması gerekir. Çalışmada da Vergi Usul Kanunu kapsamında yer alan şekil ve usul kuralları ile bunlara aykırılıklar yani usulsüzlükler incelenmiştir. Bunun öncesinde usulsüzlük fiillerinin, suç-kabahat ayrımındaki yeri ve usulsüzlüklere uygulanacak yaptırımların niteliği tespit edilmiştir. Sonuç olarak usulsüzlük fiillerine ilişkin düzenlemelerdeki eksiklikler ve uygulamadaki aksaklıklar konusunda çözüm önerileri sunulmuştur.

Turkish Tax System is also based on the declaration basis, as modern tax systems have adopted. Full and fair taxation based on declaration is possible only if the information and documents that form the basis for this are true. In addition, the arrangement of information and documents and the reporting of information and documents must be in accordance with the form and procedural rules. In the study, the form and procedural rules within the scope of the Tax Procedure Law, and the form and irregularities in other words, irregularities were examined. Before this, the area of the acts of irregularity in the distinction between crime and misdemeanour and the feature of the sanctions imposed on the irregularities were determined. As a result, solutions were offered for the deficiencies in the regulations regarding the acts of irregularity and the problems in implementation.
Keywords: Administrative Sanction; Finance; Hukuk; İdari Yaptırım; Kabahat Irregularity; Law; Maliye; Misdemeanor; Özel Usulsüzlük; Sprecial Irregularity; Usulsüzlük